The Rationale for the Intra-Articular Administration of Clodronate in Osteoarthritis - Moretti, Antimo (Int J Mol Sci, 2021)
Background: Several pharmacological therapeutic approaches have been proposed to manage osteoarthritis (OA), including intra-articular (IA) injections. Although the discovery of clodronate, a bisphosphonate, dates back to the 1960s and the effects of its IA administration have been investigated for decades in animal models, mechanisms of action of this drug are not quite clear, particularly in OA. This scoping review is an overview of the biological as well as the clinical role of clodronic acid in OA. Method: A scoping review based on the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) model was performed to characterize the mechanisms of action of IA clodronate in OA and to evaluate its efficacy from a clinical point of view. Results: Several effects of clodronate have been observed in animal models of OA, including depletion of synovial lining cells that results in reduced production of chemokines (IL-1, TNF- α), growth factors (TGF-β, BMP 2/4), and metalloproteases (MMP 2/3/9); prevention of cartilage damage, synovial hyperplasia, and proteoglycans loss; reduction in joint inflammation, joint swelling, and osteophyte formation. From a clinical perspective, patients with knee OA treated with IA clodronate experienced improvements in pain and joint mobility. Conclusion: Clodronate appears to have different mechanisms of action interfering with the pathogenic processes contributing to OA development and progression. This intervention demonstrated positive effects for patients affected by knee OA.